Genome-Wide SNPs Mining and Annotation in Bubalus bubalis - Anmol; Khushboo Yadav; Shiv Kumar Yadav; Vibhu Maurya; Vishal Jaishawal; Jaswant Singh; Saket K Niranjan (Archives of Current Research International, 2025)
This study aimed to identify single nucleotide polymorphisms (SNPs) in the Murrah buffalo, often referred to as the "black gold of India," using the reduced representation sequencing technique.DNA was extracted and sequenced using the ddRAD technique from blood samples taken from 96 unrelated Murrah buffalo. After processing the sequenced genomic data with various bioinformatics tools, a total of 855,563 SNPs were identified in the Murrah buffalo genome, using the Bubalus bubalis genome as a reference. Annotation revealed that the majority of these variations were located in intronic regions (67.49%), followed by intergenic regions (20.15%). The SNPs identified in this study have the potential to serve as molecular markers for economically significant traits and could be valuable for future breed improvement and conservation efforts.